DESAIN DIDAKTIS KUBUS DAN BALOK UNTUK MENGEMBANGKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP - Gita Safitri, - (2022)
Cube and cuboid are one of mathematical topics that are related to everyday life, this is because problems regarding these materials can be encountered in everyday life. Based on previous research and preliminary studies that have been carried out, the learning applied by teachers is only guided by textbooks published by the government as teaching materials used by teachers, this is one of the causes of the discovery of students experiencing learning obstacles. The purpose of this research is to create a didactical design of surface area and volume of cube and cuboid that can develop mathematical representation skills of junior high school students. The subjects of this study were class VIII students at one of the Junior High Schools (SMP) in Jambi City, Jambi Province. Data analysis in this study includes data analysis before learning (prospective analysis stage), data analysis during learning (metapedadidactic analysis stage), and analysis after learning (retrospective analysis stage). The results of the study showed that learning with teaching materials in the form of textbooks from the government was teacher-centered, so that there was no situation for action, formulation, validation, and institutionalization. The implementation of such learning has the potential to create learning obstacles in students, including the discovery of formulas made by the teacher (didactic obstacles), student's difficulties in solving mathematical representation problems that are not directly known to the length of the cube or cuboid side (epistemological obstacles), and the low motivation of students in following the learning process (ontogenic obstacles). The hypothetical didactic design of surface area and volume of cube and cuboid emphasizes that students can play an active role in concept discovery, so that through this design they can minimize learning obstacles and can develop student's mathematical representation skills.